2022
DOI: 10.1016/j.nonrwa.2021.103405
|View full text |Cite
|
Sign up to set email alerts
|

Existence and uniqueness of maximal strong solution of a 1D blood flow in a network of vessels

Abstract: We study the well-posedness of a system of one-dimensional partial differential equations modeling blood flows in a network of vessels with viscoelastic walls. We prove the existence and uniqueness of maximal strong solution for this type of hyperbolic/parabolic model. We also prove a stability estimate under suitable nonlinear Robin boundary conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…In this case, the diffusive effect induced by the viscous term makes the system of hyperbolic/parabolic nature. In fact, as pointed out by the authors in [23], for the Kelvin-Voigt blood flow model, even if the hyperbolic nature of this system is dominant, because the viscous term is small compared to other terms, this additional viscous term plays an important role in numerical simulations [29], in estimation problems [6], and when data coming from numerical models are compared with in vivo data [2]. The authors in [1] also observed this phenomenon.…”
Section: The Problemmentioning
confidence: 87%
See 3 more Smart Citations
“…In this case, the diffusive effect induced by the viscous term makes the system of hyperbolic/parabolic nature. In fact, as pointed out by the authors in [23], for the Kelvin-Voigt blood flow model, even if the hyperbolic nature of this system is dominant, because the viscous term is small compared to other terms, this additional viscous term plays an important role in numerical simulations [29], in estimation problems [6], and when data coming from numerical models are compared with in vivo data [2]. The authors in [1] also observed this phenomenon.…”
Section: The Problemmentioning
confidence: 87%
“…In this paper, we consider the following one-dimensional blood flow model in a network of vessels with viscoelastic walls (see [5,23]):…”
Section: The Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Even so, the hyperbolic nature of the system (1.1) is still dominant in the blood flow model. Recently, Maity [14] showed that the existence and uniqueness of maximal strong solutions of the system. For other results concerning numerical simulations of this model, we refer to the interesting works [1,2,5,17,22,23].…”
Section: Introductionmentioning
confidence: 99%